ON THE QUESTION OF PUBLIC MONITORING OF NORMATIVE LEGAL ACTS - Asel Gabidenovna, Казбаева (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article considers the issues of civic monitoring statutory instruments as a scientific study challenge and the function of state control.